Knowledge of rabies prophylaxis among junior doctors in a tertiary hospital in Manipur - A cross-sectional study - Kh Sonarjit Singh; Vijaya Elangbam; Toijam Gambhir Singh (Wolters Kluwer Medknow Publications, 2023)
Context: Rabies, a zoonotic disease caused by Lyssavirus genus rabies virus, is 100% fatal yet preventable. Appropriate and timely management of rabies cases will help in reducing and preventing mortality. Health-care personnel, especially the junior doctors who are at the threshold of their public health service, need to be equipped with adequate knowledge to be able to provide effective care. Aims: The aims of the study are to assess the knowledge about rabies and to assess the association between knowledge with sociodemographic characteristics among the junior doctors of a tertiary care hospital, Imphal. Settings and Design: A cross-sectional study was conducted among 520 junior doctors of a tertiary care hospital including interns, house officers, and postgraduate trainees from June 2018 to July 2019. Subjects and Methods: Data collection was done by questionnaire method. Statistical Analysis Used: The data were analyzed using IBM SPSS for Windows, Version 21.0. Armonk, NY, USA. Results: Only 17.5% of the junior doctors had adequate knowledge about rabies. Those who had come across and those who had treated rabies were 35.4% and 23.7%, respectively. Only around half of the respondents knew the management of the WHO Category I and III animal bite exposure. Conclusions: In the present study, it was seen that the overall knowledge of the junior doctors was poor. Only 2 out of 10 of the participants had adequate knowledge of rabies. One-fourth of the participants had treated rabies in their clinical practice and those who had treated rabies had better knowledge compared to those respondents who had never treated.